2013
DOI: 10.1177/0954407012467288
|View full text |Cite
|
Sign up to set email alerts
|

Switchable dual-port casing treatment scheme for an enhanced turbocharger compressor operating range

Abstract: For both diesel and gasoline internal-combustion engines, stringent emissions regulations and fuel economy requirements have significantly intensified the demand on the turbocharger compressor operating flow range with high efficiency levels. To address these needs, the ongoing research and development effort has been focused on advanced turbocharger technologies for a high efficiency and a wide operating range. In this paper, a research effort is reported to enhance further the classic ported shroud or recirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Furthermore, Zheng et al 4 tried to address the non-axisymmetric pressure distribution of a centrifugal compressor by including a ported shroud whereby the slot position within the impeller passage varied axially; more recently, Wang et al 5 showed that the non-axisymmetric placement of vanes in the cavity can improve the impeller and diffuser flow fields towards surge. More complex systems were also reported by Tomita et al 6 and Sun et al 7 Tomita combined a ported shroud with inlet guide vanes which improved map width but sacrificed efficiency, and Sun added a second slot in the impeller passage to further increase the maximum capacity (but this system was no longer passive). All of these devices have an annular cavity which extends axially towards the compressor inlet pipe (Figure 2(a)), and the problem with this is the design space.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, Zheng et al 4 tried to address the non-axisymmetric pressure distribution of a centrifugal compressor by including a ported shroud whereby the slot position within the impeller passage varied axially; more recently, Wang et al 5 showed that the non-axisymmetric placement of vanes in the cavity can improve the impeller and diffuser flow fields towards surge. More complex systems were also reported by Tomita et al 6 and Sun et al 7 Tomita combined a ported shroud with inlet guide vanes which improved map width but sacrificed efficiency, and Sun added a second slot in the impeller passage to further increase the maximum capacity (but this system was no longer passive). All of these devices have an annular cavity which extends axially towards the compressor inlet pipe (Figure 2(a)), and the problem with this is the design space.…”
Section: Introductionmentioning
confidence: 85%
“…6 and Sun et al. 7 Tomita combined a ported shroud with inlet guide vanes which improved map width but sacrificed efficiency, and Sun added a second slot in the impeller passage to further increase the maximum capacity (but this system was no longer passive). All of these devices have an annular cavity which extends axially towards the compressor inlet pipe (Figure 2(a)), and the problem with this is the design space.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical study revealed that [12] the introduction of split blades may introduce shock wave induced blockages at near choke conditions and unlike the other viscous related aerodynamic blockages, these shock wave induced blockages near the leading edge of splitters may be utilized to extend the choke flow capacity. Figure 3 illustrates the CFD predicted flow field of a transonic compressor impeller near choke condition.…”
Section: Fig 1 Customer Driving Cycles and Rated Power Conditions Rmentioning
confidence: 97%
“…Extensive numerical analyses have greatly assisted the optimization process, leading to advanced compressor and mixed-flow turbine that has superior efficiency over wide operation range [12].…”
Section: Fig 1 Customer Driving Cycles and Rated Power Conditions Rmentioning
confidence: 99%
“…The surge margin of turbocharger compressor was extended without much decrease in the efficiency. Hu et al 4 and Sun et al 5 investigated the switchable dual-port casing treatment for a turbocharger compressor. The underlying mechanism of the self-recirculation casing treatment technology was investigated with computational fluid dynamics modeling and bench testing.…”
Section: Introductionmentioning
confidence: 99%